2021
DOI: 10.1080/21655979.2021.1957754
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin β-A (INHBA) induces epithelial–mesenchymal transition and accelerates the motility of breast cancer cells by activating the TGF-β signaling pathway

Abstract: Inhibin β-A (INHBA) induces epithelial-mesenchymal transition and accelerates the motility of breast cancer cells by activating the TGF-β signaling pathway,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 42 publications
3
35
0
Order By: Relevance
“…Among the first ten top-ranked primary INHBA interactors in the STRING protein-protein interaction (PPI) network, most genes were involved in the TGF- β signaling pathway. Previous studies have also demonstrated that INHBA plays a role in the regulation of cancer cell growth, proliferation, and survival via the TGF- β signaling pathway Chen et al (2019) ; Yu et al (2021) ; Basu et al (2015) . GO and GSEA analysis revealed that INHBA -related genes were associated with extracellular matrix, collagen formation and degradation, the misregulation of which is a key factor in epithelial to mesenchymal transition (EMT) Burke et al (2015) .…”
Section: Disscusionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the first ten top-ranked primary INHBA interactors in the STRING protein-protein interaction (PPI) network, most genes were involved in the TGF- β signaling pathway. Previous studies have also demonstrated that INHBA plays a role in the regulation of cancer cell growth, proliferation, and survival via the TGF- β signaling pathway Chen et al (2019) ; Yu et al (2021) ; Basu et al (2015) . GO and GSEA analysis revealed that INHBA -related genes were associated with extracellular matrix, collagen formation and degradation, the misregulation of which is a key factor in epithelial to mesenchymal transition (EMT) Burke et al (2015) .…”
Section: Disscusionmentioning
confidence: 97%
“…Among the first ten top-ranked primary INHBA interactors in the STRING protein-protein interaction (PPI) network, most genes were involved in the TGF-β signaling pathway. Previous studies have also demonstrated that INHBA plays a role in the regulation of cancer cell growth, proliferation, and survival via the TGF-β signaling pathwayChen et al (2019);Yu et al (2021);Basu et al (2015).GO and GSEA analysis…”
mentioning
confidence: 99%
“…INHBA is reported to be involved in cell growth, proliferation, apoptosis, metastasis, and carcinogenesis [29][30][31][32]39]. INHBA is involved in various physiological processes through autocrine and paracrine functions [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…According to several studies, the overexpression of INHBA is associated with lung, esophageal, colon, gastric, prostate, and urothelial carcinoma [23][24][25][26][27][28]. INHBA has been identified to have a crucial role in malignant biological behavior, including proliferation, migration, invasion, and metastasis [29][30][31][32]. Previous studies revealed that the overexpression of INHBA may be affected by promoter methylation in cancer [23,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, the induction of EMT is associated with tumor aggressiveness and poor prognostic outcomes in breast cancer patients [ 65 , 66 ]. The role of chemokines in EMT induction in epithelial tumor cells has been investigated [ 67 , 68 ], and the evidence has implicated CCL20 in such processes [ 69 ]. In vitro study has demonstrated that direct coculture between healthy breast cells and recombinant human CCL20 upregulates vimentin and N-cadherin, which are characteristics of EMT.…”
Section: Role Of Ccl20 In Breast Cancer Progressionmentioning
confidence: 99%